Temporal variation in the cloud-top temperature of Venus revealed by meteorological satellites - Gaku Nishiyama; Yudai Suzuki; Shinsuke Uno; Shohei Aoki; Tatsuro Iwanaka; Takeshi Imamura; Yuka Fujii; Thomas G. Müller; Makoto Taguchi; Toru Kouyama; Océane Barraud; Mario D’Amore; et al. (Earth, Planets and Space)
Abstract Temporal variations in the cloud-top temperature of Venus are essential observable for understanding its atmospheric dynamics and related phenomena, such as thermal tides and planetary-scale waves. While multiband monitoring of both phenomena over years could hint at ongoing dynamics, spaceborne observations of Venus over the last decade are limited to single-band imagery or short timeframe. As a complementary data for the lack of decadal multiband infrared measurements of Venus, the Japanese meteorological satellites Himawari-8/9 may be utilized because they have been coincidentally imaging Venus in space adjacent to the Earth’s rim. These images can serve as a new dataset for both Venus science and instrument calibrations in planetary missions, though they have never been utilized for such purposes. This study first archived all the Venus images taken by Himawari-8/9 from July 2015 to February 2025 and succeeded in retrieving disk-normalized brightness temperatures and their temporal variation on day to year scales. The archived data were compared with other observations from the Akatsuki and BepiColombo missions. Our comparison shows that the long-wave infrared camera (LIR) on Akatsuki has underestimated the infrared radiance by 15–17%, which needs to be considered in future LIR data analyses. From comparisons of the observed temperatures at each local time on Venus, we also found that the retrieved temporal variations contain changes in the patterns of thermal tides. Particularly at sunrise, the observed brightness temperatures were not constant between 2015 and 2024, implying variations in the amplitude of diurnal thermal tides. Furthermore, the amplitude of the 5-day Rossby waves decreased at altitudes of 68 km or higher, as suggested by previous numerical circulation models. Although retrieval of the Rossby-wave amplitude was successful only in two observation periods, a variation in altitude dependence was confirmed between 2015 and 2024. These observed temporal variations may be caused by several factors, including a change in static stability observed in the Himawari-8/9 measurements. These results demonstrate that meteorological satellites can serve as additional eyes to access the Venusian atmosphere from space and complement future observations from planetary missions and ground-based telescopes. Graphical Abstract